Bibliometric Analysis of Literature on Digital Banking and Financial Inclusion Between 2014-2020 - Muhammad Ridhwan Ab. Aziz; Mohd Zalisham Jali; Mohd Nazri Mohd Noor; Syahnaz Sulaiman; Mohd Shukor Harun; Muhammad Zakirol Izat Mustafar (University of Nebraska-Lincoln, 2024)
Indexed by SCOPUS/ERA